Arahan Setting Bangunan Di Kawasan Gejayan Akibat Perubahan Fungsi Rumah Tinggal Ke Komersial Kasus - , Risnawati, ST; , Prof.Ir.Bambang Hari W,MUP.,MSc.,Ph.D, ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The functional change of building, from that of residential to commercial, affects the physical environment. Such a functional change is apparently unplanned